2006
DOI: 10.2337/diacare.29.02.06.dc05-1418
|View full text |Cite
|
Sign up to set email alerts
|

Additive Beneficial Effects of Fenofibrate Combined With Candesartan in the Treatment of Hypertriglyceridemic Hypertensive Patients

Abstract: OBJECTIVE -Mechanisms underlying fibric acid and angiotensin II type 1 receptor blocker therapies differ. Signaling from peroxisome proliferator-activated receptor ␣ may cross-talk with the angiotensin II system. We investigated vascular and metabolic responses to these therapies either alone or in combination in hypertriglyceridemic hypertensive patients.RESEARCH DESIGN AND METHODS -This was a randomized, double-blind, placebo-controlled, cross-over trial with three treatment arms (each 2 months) and two wash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 36 publications
1
35
0
1
Order By: Relevance
“…Assays for plasma insulin, malondialdehyde, adiponectin, leptin, and resistin were performed in duplicate by immunoradiometric assay or by enzymel i n k e d i m m u n o s o r b e n t a s s a y a s previously described (11)(12)(13). Quantitative insulin sensitivity check index (QUICKI) was calculated as described (14).…”
Section: Research Design Andmentioning
confidence: 99%
See 2 more Smart Citations
“…Assays for plasma insulin, malondialdehyde, adiponectin, leptin, and resistin were performed in duplicate by immunoradiometric assay or by enzymel i n k e d i m m u n o s o r b e n t a s s a y a s previously described (11)(12)(13). Quantitative insulin sensitivity check index (QUICKI) was calculated as described (14).…”
Section: Research Design Andmentioning
confidence: 99%
“…Quantitative insulin sensitivity check index (QUICKI) was calculated as described (14). Imaging studies of the right brachial artery were performed by ultrasound as described (11)(12)(13).…”
Section: Research Design Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we first reported that fenofibrate significantly reduced SBP by 3 mm Hg (P=0.007) and DBP by 3 mm Hg (P=0.033) after 2 months' administration in hypertriglyceridemic, hypertensive patients when compared with baseline SBP 142 and DBP 90 mm Hg. 2 In a different study of ours in patients with primary hypertriglyceridemia, 3 fenofibrate did not significantly reduce SBP and DBP. Ten among 46 patients were mildly hypertensive.…”
Section: To the Editormentioning
confidence: 99%
“…Fenofibrate combined with candesartan improves endothelial function and reduces inflammatory markers to a greater extent than monotherapy in hypertriglyceridemic, hypertensive patients. 6 Thus, there is a strong and growing scientific rationale for recommending a combination of PPAR-␣ or PPAR-␥ and angiotensin II type I receptor blockers to prevent atherosclerosis and coronary heart disease. 2 …”
Section: Combination Therapy For Treatment or Prevention Of Atherosclmentioning
confidence: 99%